GAYA KEPEMIMPINAN KEPALA SEKOLAH PADA SEKOLAH UNGGUL (Studi di SMA Negeri 1 Sumatera Barat) - Ilda Andrian (Universitas Negeri Padang, 2014)
This study aimed to obtain information leadership style SMA Negeri 1 (effective) West Sumatra. The population of this study were 35 teachers and 30 the number of samples. Data collection tool was a questionnaire Likert scale models that have been tested for validity and reliability. Analysis using the average formula. The results of this study indicate that the head of State High School 1 West Sumatra tend to apply the transformational leadership style (3,66) compared to the transactional leadership style (3,32) and laissez-faire leadership styles (2,69). Keyword: headmaster’s leadership style